TOTAL RESISTANCE PREDICTION OF SELF PROPELLED COAL BARGE (SPCB) USING COMPUTATIONAL FLUID DYNAMIC - Purwana, Agung; Husodo, Adi Wirawan (Department of Naval Architecture - Diponegoro University, 2015)
In the present paper the computational fluid dynamic (CFD) technique is applied to predict the total resistance (Rt) of Self Propelled Coal Barge (SPCB). The simulation process was executed using ANSYSÂ®software based on fluid flow (CFX) solver. The selected CFD method is volume of fluid (VOF). The solid modeling of SPCB is developed using MaxsurfÂ®. Boundary conditions are set on each domain area covering bottom,free surface, inlet, outlet, shipand wall. The variation of computaitional grid (meshing grid) which is used in computation are SST (Shear Stress Transport)67,000, SST 73,000, SST 103,000, SST 117,000, SST 127,000, SST 147,000, SST 157,000, and SST 200,500. Total resistance (Rt) resulted from CFX computation is validated with total resistance (Rt) resulted from Holtrop. The larger of grid meshing size, the better of validation result. The CFD technique demonstrated good agreement with Holtrop formulae in predicting the total resistance (Rt) of SPCB.